Transitivity Analysis on Sri Mulyani’s Speech at Singapore Summit: A Systemic Functional Linguistics Perspective - Saputra, Nanda; Fatmawati, Endang; Ngongo, Magdalena; Herman, Herman; Thao, Nguyen Van (Humanus, 2022)
This research discusses transitivity process in the speech of Sri Mulyani. This research aims to classify the type of transitivity process. This research employed systemic functional linguistics theory of Halliday, particularly transitivity system as a tool of analysis, more specific this research analyzed process of transitivity. The data collected from Sri Mulyani’ speech at Singapore Summit. The researchers used qualitative research design to answer the research question and chose content analysis because the result of the data analyzed is in descriptive phenomenon such as word, clause and utterance. The researchers used documentation as the research instrument. The researchers collected the data that is posted on September, 14th 2014. The findings of this research showed that material process was 44,29%, mental process was 24,29%, relational process was 25%, verbal process was 2,14%. behavioural process was 2,86% and existential process was 1,42%, so dominant process used on the speech was material process, the material process found 62 times with percentage 44,29 %. This research concluded that Sri Mulyani tended to use material process, in contrast with existential process which only have 1,42% as the lowest process in the speech. It showed that Sri Mulyani prefers to show the action and told what will they do for the next time.